Knowledge, Attitude and Practices on Childhood Immunisation among Parents Attending Paediatric OPD at a Tertiary Care Centre, Kanchipuram District, Tamil Nadu, India - Parvathy Devi; Sowjan Manohar; R Lavanya; Sekar Pasupathy (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Vaccine-preventable diseases (VPD) are considered one of the leading causes of sicknesses and deaths among children worldwide. Parents' knowledge and attitude towards immunisation are likely to influence uptake. Vaccination is one of the most cost-effective public health tools to prevent infectious diseases. Aim:This study assessed parents' knowledge, attitudes, and practice towards their children's vaccination. Materials and Methods: A cross-sectional study was conducted in the Department of Paediatrics, at Karpaga Vinayaga Institute of Medical Sciences and Research, Chengalpattu, Tamil Nadu, India from April 2019 to June 2019. Two hundred and sixty-six parents of 0 to 12-year-old children, attending the paediatric Outpatient Department (OPD), were recruited for the study. A prestructured questionnaire on knowledge, attitude, and practices regarding immunisation was administered, and other socio-demographic details were collected. Descriptive analysis was done by frequency and percentage. Data entry and analysis were performed in Microsoft Excel. Results: Among the 266 parents studied, a majority 129 (48.5%) of the mothers were 26 to 30 years old, and fathers were in the age group of 31-35 years 98 (36.8%). The majority 89 (33.5%) of the fathers were semi-skilled workers, and mothers were unskilled workers 180 (67.7%). Overall, 36.5% of children were 6 to 10 years old, and 53.4% were male children. Among the parents, 98.1% stated vaccines were safe, 95.1% knew that vaccine would prevent their children from diseases. 99.2% agreed that all children should be vaccinated, 96.2% maintained a vaccination card, 81.2% were aware of the following vaccination date for their children. Conclusion: According to the present study findings, there is generally good knowledge, attitude, and practices regarding vaccination of children among their parents. Knowledge regarding optional vaccinations needs to be improved through creating awareness.